A kind of fluorescence detection method of copper ions

By solidly loading copper ions and rhodamine B onto the amino-functionalized zirconium dioxide nanotube array film, the disadvantages of the existing liquid phase detection method are solved, and efficient and low-cost copper ion fluorescence detection is achieved, with good Detection performance and carrier renewability.

CN114563384BActive Publication Date: 2025-02-07HEBEI UNIV OF TECH

Patent Information

Application Number
CN202210205936.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-28
Publication Date
2025-02-07
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

The existing copper ion fluorescence detection method is carried out in the liquid phase, and has the disadvantages of solvation affecting the detection performance, large waste liquid volume, easy contamination, solid particles settled, and reduced uniformity.

Method used

The amino-functionalized zirconium dioxide nanotube array thin film was used as a carrier to solidly load copper ions and rhodamine B onto the carrier to prepare detection samples, and the detection of copper ions was achieved by testing the fluorescence intensity.

Benefits of technology

This method is simple and easy to use, has good detection performance, low cost, low waste liquid, can regenerate and reuse the carrier, greatly improves the fluorescence emission intensity, and improves the sensitivity, detection limit and detection range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114563384B_ABST
    Figure CN114563384B_ABST
Patent Text Reader

Abstract

The present invention is a method for fluorescent detection of copper ions. The method uses an amino-functionalized zirconium dioxide nanotube array film as a carrier and rhodamine B as a fluorescent probe, and immobilizes copper ions and rhodamine B on the amino-functionalized zirconium dioxide nanotube array film carrier to prepare a detection sample, and the detection of copper ions can be achieved by testing the fluorescence intensity of the detection sample. The method is simple and easy to implement, has good detection performance, low cost, small amount of waste liquid, and the amino-functionalized zirconium dioxide nanotube array film carrier can be regenerated and reused.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of analysis and detection, and particularly relates to a fluorescence detection method for copper ions. Background Art

[0002] Since heavy metals are widely used in many fields, a large amount of heavy metal ions enter the water, causing heavy metal ion pollution, which will cause serious harm to human health, animals and plants. For example, copper is an important component of human health and many biological tissues. This trace nutrient plays a vital role in bone formation, cell respiration, and the synthesis of hemoglobin and elastin; however, if copper ions cannot be maintained at an appropriate physiological concentration, it will lead to serious syndromes such as osteoporosis, Wilson's disease and Alzheimer's disease.

[0003] Detection of heavy metal ions is the basis for preventing and controlling heavy metal ion pollution. Therefore, detection of copper ions is of great significance. At present, there are many methods for detecting copper ions, such as atomic absorption spectrophotometry, electrochemical method, plasma emission spectroscopy, fluorescent probe method, etc. Among them, the fluorescent probe method has the characteristics of high sensitivity, fast response speed and simple operation.

[0004] There have been reports on the detection of copper ions by fluorescent probes. For example, Dyes and Pigments (2013, 99, P472-479) reported a method for fluorescent detection of copper ions. It used rhodamine B hydrazide and 4-chloro-7-nitro-2,1,3-benzoxadiazole as raw materials to synthesize a new type of rhodamine dye. When the dye was used as a fluorescent probe to detect copper ions, it showed high selectivity and sensitivity. Sensors and Actuators B: Chemical (2013, 188, P735-740) reported a method for fluorescent detection of copper ions. The method used rhodamine hydrazone and 2-pyridine formaldehyde to synthesize o-pyridine aldehyde rhodamine hydrazone. Using o-pyridine aldehyde rhodamine hydrazone as a fluorescent probe, the detection of copper ions can be achieved. "ACS applied materials & interfaces" (2014, 6, P6562-6569) reported a method for fluorescent detection of copper ions, which used fluorescein hydrazide and indole-3-carboxaldehyde as raw materials to synthesize a water-soluble fluorescein derivative, which can be used as a fluorescent probe to detect copper ions. "Sensors and Actuators B: Chemical" (2018, 258, P115-124) reported a method for fluorescent detection of copper ions, which used rhodamine B hydrazide and 2-bromo-5-formylpyridine as raw materials to synthesize a new rhodamine derivative, which can be used as a fluorescent probe to detect copper ions. "Materials Chemistry Frontiers" (2019, 3, P2437-2447) reported a method for fluorescent detection of copper ions. It synthesized coumarin-thiazolyl functionalized salicylaldehyde Schiff base in ethanol solution through condensation reaction using coumarin derivatives and salicylaldehyde. It can be used as a fluorescent probe to detect copper ions.

[0005] Most of the copper ion fluorescence detection methods reported so far are performed in liquid phase. The detection performance can be improved by synthesizing new fluorescent probes. When fluorescence detection is performed in liquid phase, the detection performance is limited due to the influence of solvation. In addition, there are disadvantages such as large amount of waste liquid and easy contamination of the system to be tested. Although adding solid particles to the liquid phase can increase the fluorescence intensity, there are disadvantages such as easy sedimentation of solid particles, reduced liquid phase uniformity, affecting detection performance, and difficult recovery of solid particles. Although the synthesis of new fluorescent probes can improve the detection performance, there are defects such as high cost and poor stability of fluorescent probes, and the disadvantages of liquid phase detection still exist. Summary of the invention

[0006] In view of the problems existing in the current fluorescent probe method for detecting copper ions, the present invention develops a fluorescent detection method for copper ions. The method uses an amino-functionalized zirconium dioxide nanotube array film as a carrier and rhodamine B as a fluorescent probe. The copper ions and rhodamine B are immobilized on the amino-functionalized zirconium dioxide nanotube array film carrier to prepare a detection sample. The detection of copper ions can be achieved by testing the fluorescence intensity of the detection sample. The method is simple and easy to implement, has good detection performance, low cost, small amount of waste liquid, and the amino-functionalized zirconium dioxide nanotube array film carrier can be regenerated and reused.

[0007] The technical solution of the present invention is:

[0008] A method for fluorescent detection of copper ions comprises the following steps:

[0009] The solution to be tested and 0.2M acetic acid-sodium acetate buffer solution (pH=5.4) are mixed in equal volumes to obtain a mixed solution, the mixed solution is coated on the surface of an amino-functionalized zirconium dioxide nanotube array film, sealed and allowed to stand for 5 to 30 minutes, and then the sample is dried at 100 to 110°C for 5 to 30 minutes, and cooled to obtain a sample solidified with copper ions; then a rhodamine B solution is coated on the sample solidified with copper ions, sealed and allowed to stand for 5 to 30 minutes, and then the sample is air-dried or blow-dried to obtain a test sample; under light of a certain excitation wavelength, the fluorescence emission intensity value of the test sample is obtained, and the copper ion content in the solution to be tested can be measured by comparing the standard curve of copper ion concentration (C) and fluorescence emission intensity (I) of the test sample under the same excitation wavelength.

[0010] Wherein, 100 microliters of the solution to be tested and the rhodamine B solution are dripped into each 2 to 8 square centimeters of the membrane; the solvent of the rhodamine B solution is anhydrous ethanol, and the concentration is 5 to 15 mg / L.

[0011] The method for obtaining the standard curve of the copper ion concentration (C) and the fluorescence emission intensity (I) of the test sample comprises the following steps:

[0012] (1) Coating a copper ion solution prepared with a 0.1M acetic acid-sodium acetate buffer solution (pH=5.4) on the surface of an amino-functionalized zirconium dioxide nanotube array film, sealing and standing for 5 to 30 minutes, then drying the sample at 100 to 110°C for 5 to 30 minutes, and cooling to obtain a sample loaded with copper ions; then coating a rhodamine B solution on the sample loaded with copper ions, sealing and standing for 5 to 30 minutes, and then air-drying or blowing the sample to obtain a test sample; obtaining the fluorescence emission intensity value of the test sample under light of a certain excitation wavelength;

[0013] (2) According to the above method, copper ion solutions of different concentrations (C) are selected to prepare test samples, and the fluorescence emission intensity (I) of these test samples is tested under the same excitation wavelength to obtain a standard curve of different copper ion concentrations (C) and the fluorescence emission intensity (I) of the test samples under the excitation wavelength, that is, a standard curve of C and I.

[0014] Wherein, 100 microliters of copper ion solution and rhodamine B solution are added to each 2 to 8 square centimeters of membrane; the copper ion concentration is 0.001 to 300 μM at intervals; the solvent of the rhodamine B solution is anhydrous ethanol, and the concentration is 5 to 15 mg / L.

[0015] The excitation wavelength is specifically 545-555 nm.

[0016] The method for preparing the amino-functionalized zirconium dioxide nanotube array film comprises the following steps:

[0017] (1) Preparation of zirconium dioxide nanotube array films

[0018] A zirconium sheet was used as the anode and a platinum sheet as the cathode. They were inserted into an electrolyte and anodized for 2 to 4 hours at a temperature of 35 to 45°C and a voltage of 25 to 35 V. After cleaning and drying, they were calcined at 400 to 600°C for 1 to 2 hours to obtain a zirconium dioxide nanotube array film on the surface of the zirconium sheet. The sample was marked as ZNAF.

[0019] The electrolyte is composed of ammonium fluoride, ammonium sulfate and deionized water, and the mass ratio is ammonium fluoride: ammonium sulfate: deionized water = 0.1-0.2: 10-15: 80-90;

[0020] (2) Amino functionalization of zirconium dioxide nanotube array films

[0021] The amino coupling agent solution is coated on the ZNAF sample, sealed and left to stand for 30 to 60 minutes, then taken out, blown dry, dried at 90 to 120° C. for 60 to 120 minutes, and cooled to obtain an amino-functionalized zirconium dioxide nanotube array film (labeled as ZNAF-NH2);

[0022] Wherein, 100 microliters of amino coupling agent solution is dripped into each 2-8 square centimeters membrane; the concentration of the amino coupling agent solution is 0.001-0.6M, and the solvent is 85-95% by volume of ethanol.

[0023] Wherein, the amino coupling agent is γ-aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane.

[0024] The size of the zirconium sheet is preferably 10-20 mm×25-35 mm×0.1-0.3 mm.

[0025] The beneficial effects of the present invention are:

[0026] (1) The outstanding feature of the present invention is that copper ions and rhodamine B are immobilized on a thin film carrier to prepare a detection sample, and the detection of copper ions can be achieved by testing the fluorescence intensity of the detection sample. The method is simple and easy to implement, has a small amount of waste liquid, and is low in cost.

[0027] (2) Another outstanding feature of the present invention is that the amino-functionalized zirconium dioxide nanotube array film is used as a carrier. Zirconium dioxide is an excellent carrier, and the zirconium oxide nanotube array has a large specific surface area and a highly ordered tubular structure. When rhodamine B is immobilized on the zirconium oxide nanotube array film, its fluorescence emission intensity is greatly improved, which is several times that of the rhodamine B aqueous solution, which is conducive to the improvement of fluorescence detection performance.

[0028] Amino groups can react with copper ions to form complexes. Amino functionalization of zirconium dioxide nanotube array films can improve the uniformity of the dispersion of copper ions and rhodamine B on the carrier surface, which is also beneficial to the improvement of fluorescence detection performance.

[0029] (3) The significant feature of the present invention is that rhodamine B is used as a fluorescent probe. Rhodamine B is a commonly used fluorescent dye with stable performance and low price.

[0030] (4) The significant feature of the present invention is that the carrier can be regenerated and reused by soaking and washing with a 0.1-0.5M acetic acid solution, and the relative standard deviation (RSD) of the carrier reuse is less than 4%.

[0031] (5) The salient feature of the present invention is that it has good fluorescence detection performance for copper ions, with a sensitivity, detection limit and detection range of up to 1200, 0.8 nM and 0.001-300 μM respectively.

[0032] (6) The present invention has the remarkable feature of having good anti-interference performance. + , Hg 2+ , Pb 2+ 、Cd 2+ , Ca 2+ 、Zn 2+ Mg 2+ , K + 、SO4 2- , Cl - ) in the presence of , the RSDs were all lower than 6%. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the surface morphology of the zirconium dioxide nanotube array film (ZNAF) prepared in Example 1 of the present invention.

[0034] Figure 2 The curve of the fluorescence emission intensity (I) of the test sample obtained in Example 1 of the present invention versus the copper ion concentration (C) (I-logC curve, excitation wavelength 550 nm).

[0035] Figure 3 This is the fluorescence emission spectrum (excitation wavelength 550nm) of a mixed solution of rhodamine B (10mg / L) and different concentrations of copper ions (0.001-300μM) prepared in 0.1M acetic acid-sodium acetate buffer solution (pH=5.4).

[0036] The present invention will be further described below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION

[0037] The testing principle of the present invention is as follows:

[0038] The excited state of Rhodamine B has a strong redox ability. Copper ions will catalyze the oxidation reaction between oxygen in the air and Rhodamine B, causing fluorescence quenching. As the concentration of copper ions increases, the amount of Rhodamine B participating in the oxidation reaction and causing fluorescence quenching increases. Therefore, the fluorescence emission intensity of the test sample decreases, thereby achieving the detection of copper ions.

[0039] Example 1

[0040] (1) Ultrasonic clean the zirconium sheet (15mm×30mm×0.2mm) with ethanol and deionized water. Weigh 0.1g of ammonium fluoride and 13.2g of ammonium sulfate, add them to 86.7g of deionized water, stir to dissolve, and prepare the electrolyte. Insert the lower 20mm of the zirconium sheet into the electrolyte, with the zirconium sheet as the anode and the platinum sheet as the cathode, and perform anodization at 40°C and 30V for 3 hours. After the reaction is completed, wash the sample with deionized water, dry it, and calcine it at 500°C for 2 hours to obtain a zirconium dioxide nanotube array film (ZNAF) with a surface morphology as shown below. Figure 1 As shown in the figure, it can be seen that the ZNAF has a flat surface, uniform structure, small tube diameter (about 25nm), and large tube mouth spacing. This morphology is conducive to the deposition, dispersion and fluorescence detection of rhodamine B.

[0041] (2) Add γ-aminopropyltriethoxysilane to 90% (volume percentage) ethanol, stir and dissolve evenly, and prepare an amino coupling agent solution with a concentration of 0.2 M. Place the sample ZNAF horizontally in a weighing bottle, take 100 microliters of the amino coupling agent solution and evenly drop it on the top of the ZNAF membrane, cover the bottle cap, let it stand for 60 minutes, then take out the sample, blow dry, dry at 110°C for 90 minutes, and cool to obtain an amino-functionalized zirconium dioxide nanotube array film (ZNAF-NH2).

[0042] (3) Detection of copper ions

[0043] ① Use 0.1M acetic acid-sodium acetate buffer solution (pH=5.4) to prepare copper ion solutions with concentrations of 0.001, 0.01, 0.1, 1, 10, 100, and 300 μM, and use rhodamine B and anhydrous ethanol to prepare a rhodamine B solution with a concentration of 10 mg / L.

[0044] ② Place the sample ZNAF-NH2 horizontally in a weighing bottle, take 100 microliters of copper ion solution and evenly add it onto the ZNAF-NH2 membrane, cover the bottle cap, let it stand for 20 minutes, then dry the sample coated with copper ions at 110°C for 10 minutes and cool it; place the sample coated with copper ions horizontally in a weighing bottle, take 100 microliters of rhodamine B solution and evenly add it onto the sample, cover the bottle cap, let it stand for 20 minutes, then blow it dry with a blower at room temperature to obtain the test sample.

[0045] ③ Under the condition of an excitation wavelength of 550nm (FL-7000 fluorescence spectrophotometer, Hitachi, Japan), the fluorescence emission intensity (I) of the test sample prepared with different concentrations (C) of copper ion solution was tested, and the I~logC curve was drawn, as shown in FIG. Figure 2 As shown; the I~logC curve can be fitted into a straight line, the correlation coefficient is 0.998, and the linear equation is I=1944.54-563.07logC, indicating that the fluorescence emission intensity of the test sample is linearly related to the logarithm of the copper ion concentration.

[0046] ④ Use copper sulfate and tap water to prepare a solution with a copper ion concentration of 1.0 μM as the test solution, mix this solution with equal volumes of 0.2 M acetic acid-sodium acetate buffer solution (pH = 5.4), use this mixed solution to prepare a test sample according to the conditions of ②, and test the fluorescence emission intensity of the test sample at an excitation wavelength of 550 nm (I = 2106). From the linear equation, it can be obtained that C = 0.517 μM. Therefore, the measurement result of the copper ion concentration of the original solution is 2×C = 1.034 μM, and the detection deviation is 3.4%.

[0047] Add 10 μM common interfering ions (Na + , Hg 2+ , Pb 2+ 、Cd 2+ , Ca 2+ 、Zn 2+ Mg 2 + , K + 、SO4 2- or Cl - ), the test samples were prepared using solutions containing interfering ions, and the RSD of each test sample was lower than 5.5%.

[0048] In order to prove the effectiveness of the present invention, a mixed solution containing 10 mg / L rhodamine B and different concentrations of copper ions was prepared with 0.1 M acetic acid-sodium acetate buffer solution (pH=5.4), and the fluorescence emission spectrum of each mixed solution was tested at an excitation wavelength of 550 nm. Figure 3 As shown, when the copper ion concentrations are 0, 0.001, 0.01, 0.1, 1, 10, 100, and 300 μM, respectively, the emission spectra of the mixed solutions are similar, the curves overlap each other, and their fluorescence emission intensities do not change significantly. Figure 3 The results showed that Rhodamine B solution could not be used to directly detect copper ions by fluorescence.

[0049] Example 2

[0050] (1) ZNAF was prepared using the same process conditions and steps as in Example 1 (1) and calcined at 400°C for 2 hours.

[0051] (2) An amino coupling agent solution with a concentration of 0.5 M was prepared using γ-aminopropyltrimethoxysilane and 95% (volume percentage) ethanol. Other conditions and steps were the same as those in Example 1 (2) to prepare ZNAF-NH2.

[0052] (3) A 15 mg / L rhodamine B solution is used to prepare a test sample, and the same process steps as in Example 1 (3) are used to perform fluorescence detection of copper ions.

[0053] Example 3

[0054] (1) ZNAF was prepared using the same process conditions and steps as in Example 1 (1) and calcined at 600°C for 1 hour.

[0055] (2) An amino coupling agent solution with a concentration of 0.01 M was prepared using γ-aminopropyltriethoxysilane and 85% (volume percentage) ethanol. Other conditions and steps were the same as those in Example 1 (2) to prepare ZNAF-NH2.

[0056] (3) A 5 mg / L rhodamine B solution is used to prepare a test sample, and the same process steps as in Example 1 (3) are used to perform fluorescence detection of copper ions.

[0057] Matters not covered by the present invention are known technologies.

Claims

1. A method for fluorescent detection of copper ions, characterized in that the method comprises the following steps: The solution to be tested and 0.2M acetic acid-sodium acetate buffer solution with a pH of 5.4 are mixed in equal volumes to obtain a mixed solution, the mixed solution is coated on the surface of the amino-functionalized zirconium dioxide nanotube array film, sealed and allowed to stand for 5 to 30 minutes, and then the sample is dried at 100 to 110° C. for 5 to 30 minutes, and cooled to obtain a sample solidified with copper ions; then a rhodamine B solution is coated on the sample solidified with copper ions, sealed and allowed to stand for 5 to 30 minutes, and then the sample is air-dried or blow-dried to obtain a test sample; under light of a certain excitation wavelength, the fluorescence emission intensity value of the test sample is obtained, and the copper ion content in the solution to be tested can be measured by comparing the standard curve of the copper ion concentration (C) and the fluorescence emission intensity (I) of the test sample under the same excitation wavelength; Wherein, 100 microliters of the solution to be tested and the rhodamine B solution are dripped into each 2 to 8 square centimeters of the membrane; the solvent of the rhodamine B solution is anhydrous ethanol, and the concentration is 5 to 15 mg / L.

2. The fluorescence detection method of copper ions as claimed in claim 1, characterized in that The excitation wavelength is specifically 545-555 nm.

3. The method for fluorescent detection of copper ions as claimed in claim 1, characterized in that the method for obtaining the standard curve of the copper ion concentration (C) and the fluorescence emission intensity (I) of the detection sample comprises the following steps: (1) Coating a copper ion solution prepared with a 0.1M, pH=5.4 acetic acid-sodium acetate buffer solution on the surface of an amino-functionalized zirconium dioxide nanotube array film, sealing and standing for 5 to 30 minutes, then drying the sample at 100 to 110° C. for 5 to 30 minutes, and cooling to obtain a sample loaded with copper ions; then coating a rhodamine B solution on the sample loaded with copper ions, sealing and standing for 5 to 30 minutes, and then air-drying or blowing the sample to obtain a test sample; obtaining the fluorescence emission intensity value of the test sample under light of a certain excitation wavelength; (2) According to the above method, copper ion solutions of different concentrations (C) are selected to prepare test samples, and the fluorescence emission intensity (I) of these test samples is tested under the same excitation wavelength to obtain a standard curve of different copper ion concentrations (C) and the fluorescence emission intensity (I) of the test samples under the excitation wavelength, that is, a standard curve of C and I; Wherein, 100 microliters of copper ion solution and rhodamine B solution are added to each 2 to 8 square centimeters of membrane; the copper ion concentration is 0.001 to 300 μM at intervals; the solvent of the rhodamine B solution is anhydrous ethanol, and the concentration is 5 to 15 mg / L.

4. The fluorescence detection method of copper ions as claimed in claim 1, characterized in that The method for preparing the amino-functionalized zirconium dioxide nanotube array film comprises the following steps: (1) Preparation of zirconium dioxide nanotube array films A zirconium sheet is used as an anode and a platinum sheet is used as a cathode. They are inserted into an electrolyte and anodized for 2 to 4 hours at a temperature of 35 to 45°C and a voltage of 25 to 35V. After cleaning and drying, they are calcined at 400 to 600°C for 1 to 2 hours to obtain a zirconium dioxide nanotube array film on the surface of the zirconium sheet. The sample is marked as ZNAF. The electrolyte is composed of ammonium fluoride, ammonium sulfate and deionized water, and the mass ratio is ammonium fluoride: ammonium sulfate: deionized water = 0.1-0.2: 10-15: 80-90; (2) Amino functionalization of zirconium dioxide nanotube array films The amino coupling agent solution is coated on the ZNAF sample, sealed and left to stand for 30 to 60 minutes, then taken out, blown dry, and dried at 90 to 120° C. for 60 to 120 minutes. After cooling, an amino-functionalized zirconium dioxide nanotube array film is obtained, which is marked as ZNAF-NH2; Wherein, 100 microliters of amino coupling agent solution is dripped per 2 to 8 square centimeters of membrane; the concentration of the amino coupling agent solution is 0.001 to 0.6M, and the solvent is 85 to 95% by volume of ethanol; Wherein, the amino coupling agent is γ-aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane.

5. The fluorescent detection method of copper ions as described in claim 4 is characterized in that the size of the zirconium sheet is preferably 10-20 mm×25-35 mm×0.1-0.3 mm.

Citation Information

Patent Citations

  • One-dimensional nanostructured fluorescent chemical biosensor and method for making same and uses

    CN101191794A

  • Six-membered spiro rhodamine fluorescent probe containing semicarbazide structure as well as preparation method and application of six-membered spiro rhodamine fluorescent probe

    CN113061139A

Cited By

  • Multifunctional magnetic graphene quantum dot sensor, preparation method thereof and application of multifunctional magnetic graphene quantum dot sensor in detection of Cu < 2 + > in wastewater

    CN120609794A